IMPLEMENTATION OF A PROGRAM TO INCREASE FOOD DIVERSIFICATION IN THE BONE REGENCY FOOD SECURITY SERVICE - Andi Rachmah Dina Iskandar; Didin Halim; Novayanti Sopia Rukmana (Universitas Negeri Makassar, 2026)
This study aims to determine and describe the Implementation of the Food Diversification Improvement Program at the Bone Regency Food Security Service. This type of research is qualitative descriptive research with data collection techniques through observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the food diversification improvement program at the Bone Regency Food Security Service has not run optimally. There are four dimensions that are considered in viewing the implementation of the program, namely disposition, bureaucratic structure, communication and resources. Of the four dimensions, the obstacle in the implementation of the program is the resources that are not yet optimal for Agricultural Extension Workers. In general, the implementation of the program has gone well. In the disposition dimension, all stakeholders and regional apparatus organizations participate and support the implementation of the program, in the bureaucratic structure dimension all policy makers have followed the rules, this can be seen from the lower to the upper levels together carrying out this program. In the communication dimension, stakeholders have communicated with all related parties such as the Department of Agriculture, the BKKBN Department, the Health Department, PKK, Village Heads, Village Heads, Farmer Groups, Agricultural Extension Workers, and the Community through routine meetings held twice a year.